Android-Based Islamic Religious Education Learning Media Application Design Body Removal Materials For Class Xi High School Students - Galuh Airlangga; Ahmad Buchori Muslim; Kiyoshi Nabakayashi (Yayasan Adra Karima Hubbi, 2023)
Currently, there are many technology learning media that can be used by teachers, one of which is android media. Android media has not been widely used in high school / ma corpse starters. With android media, monotonous corpse novice learning will be effective and become a special attraction for students.This study aims to 1) find out how research and development are carried out for technological developments that require developments in educational methods. 2) To know how to cope with the large number of students who are less interested in monotonous classroom learning. This research is a development research using the ADDIE development model which consists of 5 stages, but in this developer the researcher uses only 4 stages, namely analysis, design, development, and implementation. Data collection instruments in the form of questionnaires, observations / tests of learning outcomes. The results showed: 1) Producing android media products that are attractive, technology-based and in accordance with the needs of students in the development of this era. 2) The product is developed through First, needs analysis. Second, designing learning media with storyboards, thirdly developing android media then validating material experts, media, and teachers. The fourth is the implementation of the teacher in the classroom.